Needle Licker’s Osteomyelitis Revisited: An Unusual Case of Vertebral Osteomyelitis with Eikenella corrodens in a Diabetic Patient - Bianca Roth; Katrin-Elisabeth Schimke; Agnes Ruckstuhl; Fabrice Külling; Tobias Dietrich; Carol Strahm (Case Reports in Infectious Diseases)
Vertebral osteomyelitis due to Eikenella corrodens is extremely rare. We report an unusual case of an infection caused by E. corrodens in a self-insulin-administering patient with diabetes. Similar to needle licker’s osteomyelitis, our case shows most likely the same pathomechanism and stresses the importance of correct insulin application.